Double J stent malposition in the inferior vena cava: Two case reports and a literature review - Wang, Qihua; Shen, Chen; Zhang, Yue; Wen, Lijie; Yang, Bo (Frontiers in Surgery, 2022)
Double J stent (DJS) malposition in the vascular system is a rare and severe complication. We present two cases in our department who went through DJS malposition in the inferior vena cava and our experience in treatment, and we reviewed the previous case reports to further summarize its underlying reasons and prevention and treatment methods.